Lacanian psychoanalysis against psychology - Hook, Derek (PINS-Psychology in Society, 2017)
[BOOK REVIEW] Murray, Martin (2016) Lacan: A critical introduction. London: Pluto Press. ISBN 978 0745 315904 pbk. Pages 214 Martin Murray’s Lacan: A critical introduction sets itself apart from the ever-growing introductory literature on the French psychoanalyst. It breaks a number of unwritten rules that have thus far defined this genre of introductory texts. For a start, it involves a significant amount of biographical material, which it interweaves with a series of critical and historical expositions. This deviation from the norm itself poses a question: why the paucity of biographical material on Lacan compared to the apparently unending literature probing and describing various facets of Freud’s life? It is curious, given that a detailed life history plays such a crucial role in clinical psychoanalysis, that Lacanian scholars and analysts seem – with the notable exception of Elisabeth Roudinesco (1990,1997, 2014) – so averse to engaging Lacan’s biography. One answer is perhaps obvious: the transference effect apparent in many idealizations of Lacan (see for example Gérard Miller’s (2011) recent hagiographic film Rendez-vous chez Lacan) would be punctured should Lacan’s past be too thoroughly investigated. In contrast to Freud’s relatively staid life, there was, as Roudinesco’s biography tells us, no shortage of controversy in Lacan’s. One understands then the unspoken rule: for Lacanians, so it seems, one does not psychoanalyse Lacan!